The Effect of Profitability, Leverage, and Liquidity on Firm Value with Firm Size as a Moderating Variable - Muhammad Salman Alfarisy; Setyo Budi Hartono; Nurudin Nurudin (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - For know influence profitability, leverage and liquidity to mark company with size company as variables moderation in companies listed on the Jakarta Islamic Index (JII) for the 2021-2023 period. Method - Study this use approach quantitative with using secondary data. Population as many as 20 companies and samples study chosen through purposive sampling method so that acquired 15 companies. Result - Profitability and leverage have an impact positive and significant to mark Company liquidity has no effect on firm value. Firm size weakens the relationship between leverage and firm value. Firm size is unable to moderate the relationship between profitability and liquidity on firm value. Implication - This research serves as information for sharia investors in selecting companies on the Jakarta Islamic Index that are expected to have good financial performance and have investment opportunities, because financial performance in the good category will have a positive impact on both companies and investors in the future.. Originality - The increase in sharia-compliant issuers, in line with the increase in sharia investors, necessitates research into the sharia-compliant stock index category. The JII was chosen because it comprises 30 of the most liquid sharia-compliant stocks, classified by the IDX. The JII serves as a reference for investors seeking sharia-compliant investments in accordance with Islamic law. Keywords: Profitability, Leverage, Liquidity, Value, Size